2008
DOI: 10.1038/ijo.2008.152
|View full text |Cite
|
Sign up to set email alerts
|

Is sleep-disordered breathing an additional risk factor for the metabolic syndrome in obese children and adolescents?

Abstract: Sleep-disordered breathing is highly prevalent in childhood obesity. Two recent cross-sectional studies have demonstrated an independent association between the severity of sleep-disordered breathing and the metabolic syndrome. A limited number of studies have also addressed the correlation between sleep-disordered breathing and insulin resistance, the core factor of the metabolic syndrome. Cross-sectional reports in modestly obese children are in favor of an association between sleep apnea and insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 41 publications
(46 reference statements)
0
16
0
1
Order By: Relevance
“…Observational studies further reported that CPAP compliance determined a positive outcome in HOMA-IR [15], or a decrease in glycosylated haemoglobin but not HOMA-IR [17]. Data on changes in fasting insulin or HOMA-IR in children before and after adenotonsillectomy were similarly variable [27,28]. In diabetic subjects with OSA, despite several positive observational studies [6,8,11,12], a randomised controlled study reported that neither HbA 1C nor insulin sensitivity measured by the euglycemic clamp changed [14].…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies further reported that CPAP compliance determined a positive outcome in HOMA-IR [15], or a decrease in glycosylated haemoglobin but not HOMA-IR [17]. Data on changes in fasting insulin or HOMA-IR in children before and after adenotonsillectomy were similarly variable [27,28]. In diabetic subjects with OSA, despite several positive observational studies [6,8,11,12], a randomised controlled study reported that neither HbA 1C nor insulin sensitivity measured by the euglycemic clamp changed [14].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin and ghrelin, hormones involved in controlling satiation and hunger, are also linked to sleep. Therefore, partial chronic sleep loss can increase food consumption and apathy towards physical activity 20 . Recently, a study 21 conducted in Alhambra, California involving 356 fifth-grade students from six public and private schools revealed a significant association between sleep onset latency and emotional eating (p=0.30), depressive symptoms (p<0.0001), and anxiety traits (p>0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children classically represent a good clinical model for examining the relationship between SDB and glucose metabolism with limited coexistent comorbidity, even though differences between adult and paediatric OSA may have become smaller due to the current high prevalence of obesity at a young age [129]. The causal role of SDB in paediatric metabolic abnormalities is currently unclear, as indicated in a recent review [130].…”
Section: Effects Of Osa Treatmentmentioning
confidence: 99%